The urban-poor vaccination: Challenges and strategies in low-and-middle income countries - Boston Zimba; Samuel Mpinganjira; Takondwa Msosa; Fanuel Meckson Bickton (Human Vaccines & Immunotherapeutics)
Vaccination is one of the success stories of public health. The benefit of vaccination goes beyond individual protection to include promoting population well-being, improving cognitive development, and increasing economic productivity. However, the existing inequalities in the access to vaccination undermines its impact. There are significant variations in the coverage of vaccination between and within countries. Despite that urban populations have better access to health services; evidence has shown that the urban poor have the worst health indicators including vaccination uptake. Additionally, there are unique challenges affecting vaccination in urban settings, especially in urban slums. This paper has discussed key challenges some of the proposed interventions that can improve urban vaccination service delivery.